2017
DOI: 10.1128/mcb.00579-16
|View full text |Cite
|
Sign up to set email alerts
|

DeSUMOylation of Gli1 by SENP1 Attenuates Sonic Hedgehog Signaling

Abstract: The transcriptional output of the Sonic Hedgehog morphogenic pathway is orchestrated by three Krüppel family transcription factors, Gli1 to -3, which undergo extensive posttranslational modifications, including ubiquitination and SUMOylation. Here, we report that the sentrin-specific peptidase SENP1 is the specific deSUMOylation enzyme for Gli1. We show that SUMOylation stabilizes Gli1 by competing with ubiquitination at conserved lysine residues and that SUMOylated Gli1 is enriched in the nucleus, suggesting … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
12
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(12 citation statements)
references
References 52 publications
0
12
0
Order By: Relevance
“…Pias1 small ubiquitin-related modifier (SUMO) ligase was found to decrease GLI1 ubiquitination, thereby increasing GLI1 transcriptional activity in vitro [117]. Alternatively, the sentrin-specific peptidase (SENP1) is the specific deSUMOylation enzyme for GLI1 that stabilizes GLI1 through competition for conserved lysine residues [118]. Furthermore, acetylation of GLI1 at lysine residue K518 by the acetyltransferase p300/CBP reduces the transcriptional activity of GLI1 through sequestering inactive GLI1, inhibition of DNA binding, and increasing nuclear export [105,119].…”
Section: Type Iii-mechanisms Independent Of Upstream Ptch1-smo Signalingmentioning
confidence: 99%
“…Pias1 small ubiquitin-related modifier (SUMO) ligase was found to decrease GLI1 ubiquitination, thereby increasing GLI1 transcriptional activity in vitro [117]. Alternatively, the sentrin-specific peptidase (SENP1) is the specific deSUMOylation enzyme for GLI1 that stabilizes GLI1 through competition for conserved lysine residues [118]. Furthermore, acetylation of GLI1 at lysine residue K518 by the acetyltransferase p300/CBP reduces the transcriptional activity of GLI1 through sequestering inactive GLI1, inhibition of DNA binding, and increasing nuclear export [105,119].…”
Section: Type Iii-mechanisms Independent Of Upstream Ptch1-smo Signalingmentioning
confidence: 99%
“…Sentrin-specific peptidase (SENP1) was shown to specifically desumoylate Gli1 and negatively regulate Hh signaling. SENP1-mediated desumoylation promotes Gli1 ubiquitination and facilitates Gli1 nuclear export [70].…”
Section: Regulation Of Gli Proteins By Posttranslational Modificatmentioning
confidence: 99%
“…GLI transcription factors are finely regulated at the post-translational level by various modifications, such as phosphorylation (7), ubiquitination (8), acetylation (9,10) and SUMOylation (11). It has previously been demonstrated that targeting some of these GLI modifications may prove to be an additional avenue with which to inhibit HH-regulated transcriptional output (12).…”
Section: Introductionmentioning
confidence: 99%